X+28+x+36=64

Simple and best practice solution for X+28+x+36=64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+28+x+36=64 equation:


Simplifying
X + 28 + x + 36 = 64

Reorder the terms:
28 + 36 + X + x = 64

Combine like terms: 28 + 36 = 64
64 + X + x = 64

Add '-64' to each side of the equation.
64 + X + -64 + x = 64 + -64

Reorder the terms:
64 + -64 + X + x = 64 + -64

Combine like terms: 64 + -64 = 0
0 + X + x = 64 + -64
X + x = 64 + -64

Combine like terms: 64 + -64 = 0
X + x = 0

Solving
X + x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-1x' to each side of the equation.
X + x + -1x = 0 + -1x

Combine like terms: x + -1x = 0
X + 0 = 0 + -1x
X = 0 + -1x
Remove the zero:
X = -1x

Simplifying
X = -1x

See similar equations:

| x^6-125y^9= | | 4x+1/x-1=20x-3/5x-7 | | -5/2-6+9 | | 4(6x+10)=-2(x-2) | | (4/x-7)-(5/x+7)=(2/x^2-49) | | log(8)(5x+5)=log(8)(5x+2) | | 8-1/2n=12 | | (-6+34)/(-14)+2 | | f(x)=4x^2+7x-15 | | (X/2)-(2/3)=(1/4) | | 8-5x=38 | | 2/7x=-6/35 | | 2(1.5c+4)=(-1) | | 5+5(2-x)=-3(x+5) | | a/4+4=88 | | x^2-2=5x^2-12x-2 | | 4+5(2-x)=-2(x+5) | | 10v^2-53v+36=0 | | y=2x^2-11x+9 | | (X^2+9x+20)/(x+15) | | f(x)=5x^2-6x-8 | | f(x)=5x^2-6x-8 | | 3x+17y=-23 | | D=Prk | | 8x+4=26-2x | | 4(3+x)=5(4x-1)-47 | | 9z+5-2z=59-2z | | 8x-2(2-x)=13 | | (1/2)y-(2/3)=7/8 | | x-10=12-x | | 6ln(x)=-1 | | 8w*2=50 |

Equations solver categories